Pengaruh Return On Asset (ROA), Debt To Equity Ratio (DER), Dan Earning Per Share (EPS) Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Andi Annisa; Fadliah Nasaruddin; Mursalim . (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2019)
This study aims to examine the effect of return on assets, debt to equity ratio and earnings per share on stock prices at manufacturing companies listed on the Stock Exchange. Data in this study, obtained from the financial statements of manufacturing companies listed on the Stock Exchange. This study uses secondary data by way of observation by visiting the Capital Market Information Center (PIPM) Data analysis method used is multiple linear regression analysis. The results showed that the partial return on assets and earnings per share have a positive and significant effect on stock prices, while the debt to equity ratio has a negative and significant effect on stock prices